Petrogenesis of Miller Range 07273, a new type of anomalous melt breccia: Implications for impact effects on the H chondrite asteroid. (3rd July 2017) - Ruzicka, Alex M.; Hutson, Melinda; Friedrich, Jon M.; Rivers, Mark L.; Weisberg, Michael K.; Ebel, Denton S.; Ziegler, Karen; Rumble, Douglas; Dolan, Alyssa A.
Abstract: Miller Range 07273 is a chondritic melt breccia that contains clasts of equilibrated ordinary chondrite set in a fine‐grained (<5 μm), largely crystalline, igneous matrix. Data indicate that MIL was derived from the H chondrite parent asteroid, although it has an oxygen isotope composition that approaches but falls outside of the established H group. MIL also is distinctive in having low porosity, cone‐like shapes for coarse metal grains, unusual internal textures and compositions for coarse metal, a matrix composed chiefly of clinoenstatite and omphacitic pigeonite, and troilite veining most common in coarse olivine and orthopyroxene. These features can be explained by a model involving impact into a porous target that produced brief but intense heating at high pressure, a sudden pressure drop, and a slower drop in temperature. Olivine and orthopyroxene in chondrule clasts were the least melted and the most deformed, whereas matrix and troilite melted completely and crystallized to nearly strain‐free minerals. Coarse metal was largely but incompletely liquefied, and matrix silicates formed by the breakdown during melting of albitic feldspar and some olivine to form pyroxene at high pressure (>3 GPa, possibly to 15–19 GPa) and temperature (>1350 °C, possibly to ≥2000 °C). The higher pressures and temperatures would have involved back‐reaction of high‐pressure polymorphs to pyroxene and olivine upon cooling. Silicates outside of melt matrix have compositions that were relatively unchanged owing to brief heating duration.